Ergebnisse der definitiven Behandlung der Autonomie bei Jodmangelstruma - Emrich, D.; Reinhardt, M. (Nuklearmedizin - NuclearMedicine, 1989)
In order to evaluate the efficacy of, and the risk associated with, the definite treatment of euthyroid goiter with autonomy, the data of 88 patients treated between 1982 and 1986 (50 by subtotal thyroidectomy; 38 by131 l-treatment, mean radiation dose 200 Gy without protection by thyroxine) were analyzed in a retrospective study. The following criteria were used before and after treatment: the results of scintigraphy under suppression qualitatively (in focal autonomy) and quantitatively (global thyroid uptake) (TcUs), the means of FT4I, FT3I and ΕTSH after TRH, the improvement of mechanical signs and symptoms and the decrease of thyroid volume. Measured by TcUs and ΕTSH, autonomy could be removed completely in 85-90% of all patients. Surgery was slightly more successful (100%) compared to treatment by 131l (75-80%). This was also true for removal of mechanical symptoms and reduction of the goiter. The incidence of manifest hypothyroidism was greater after surgery (16%) than after1311 treatment (3%). At a higher grade of autonomy (TcUs >3,2%) surgery was more effective (95-100%) than treatment with 1311 (60-70%) but at a higher risk of hypothyroidism (24 vs 0%). It is imperative to improve the methods of estimating the amount of1311 to be administered in euthyroid goiter with autonomy. Selection of patients with autonomy in euthyroid goiter for definite treatment is difficult, since until now their risk to become hyperthyroid cannot be predicted properly.